ANALISIS HADIS KOPI: Studi Terhadap Hadis yang Diterima Sufi dari Nabi Muhammad Saw Melalui Mimpi - Rani Sukma Dewi; Ilham Mustafa (DIRAYAH : Jurnal Ilmu Hadis, 2024)
Hadith is something attributed to the Prophet Muhammad SAW, whether in words, actions, approvals, or characteristics. However, there was an instance where a hadith received through a dream was then attributed to the Prophet Muhammad SAW. In the understanding of Sufis, this is considered a hadith of the Prophet SAW. One such hadith, believed by Sufis, is the hadith about coffee received by Sayyid Al-Qudaimi. This raises the question of the quality of the coffee hadith received by the Sufi from the Prophet Muhammad SAW through a dream. This research falls into the category of qualitative research, specifically library research, using the Hadith Criticism method, which is useful for examining the quality of the sanad (chain of narrators) and matan (content) of the hadith. The result of this research is that the coffee hadith received by the Sufi from the Prophet Muhammad SAW through a dream, in terms of sanad quality, is classified as a munqati’ hadith because of the broken chain of narrators. This hadith is also classified as maudhu’ or fabricated. Furthermore, in terms of matan quality, Al-Adlabi established four criteria for matan criticism. According to these four criteria, the coffee hadith received by the Sufi through a dream falls under the category of hadiths that contradict reason, sensory perception, and history, and it does not resemble prophetic speech. Therefore, it can be stated that the coffee hadith is not authentic.